IDENTIFYING TABOO WORDS UTTERED BY THE CHARACTERS IN HITMAN’S BODYGUARD MOVIE - Khudri, Khudri; Eliwarti, Eliwarti; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this descriptive research was conducted in order to find out the taboo words in the hitman’s bodyguard movie. The data were collected using the sociolinguistic approach. The data were in the form of utterances, while the contexts of the data were the dialogues uttered by the characters in the movie. The sources of the data were the video of Hitman’s Bodyguard movie and its transcript. The data were collected by selecting dialogues containing taboo words after watching the video and matching the transcript with the video carefully. The primary instrument of this research was a data sheet. The results of this research are stated as follows. Firstly, all of the types and the function of taboo words are appear in this movie. The types are obscenity,profanity, vulgarity, ephitet and for the functions are to draw attention to oneself, to be provocative, to show contempt, and to mock authority. From four of the types that appear in the movie, obscenity become the type with the highest frequency (46.29%) 25 times, the second is vulgarity with (20.37%) 11 times, the third is ephitet with (18.51%) 10 times, and the last one is profanity with (14.81%) 8 times. From four of the functions that appear in the movie to be provocativet become the function with the highest frequency (50%) 27 times, the second is to show contempt with (27.77%), the third is to draw attention to oneself with (20.37%), and the last one is to mock authority which is onle appear once in the movie (1.85%).Key Words: Sociolinguistics, Taboo Words, Hitman’s Bodyguard Movie